Redox Regulation in Aging Lungs and Therapeutic Implications of Antioxidants in COPD - Hirofumi Kiyokawa; Yuma Hoshino; Kazuhiro Sakaguchi; Shigeo Muro; Junji Yodoi (MDPI AG, 2021)
Mammals, including humans, are aerobic organisms with a mature respiratory system to intake oxygen as a vital source of cellular energy. Despite the essentiality of reactive oxygen species (ROS) as byproducts of aerobic metabolism for cellular homeostasis, excessive ROS contribute to the development of a wide spectrum of pathological conditions, including chronic lung diseases such as COPD. In particular, epithelial cells in the respiratory system are directly exposed to and challenged by exogenous ROS, including ozone and cigarette smoke, which results in detrimental oxidative stress in the lungs. In addition, the dysfunction of redox regulation due to cellular aging accelerates COPD pathogenesis, such as inflammation, protease anti-protease imbalance and cellular apoptosis. Therefore, various drugs targeting oxidative stress-associated pathways, such as thioredoxin and N-acetylcysteine, have been developed for COPD treatment to precisely regulate the redox system. In this review, we present the current understanding of the roles of redox regulation in the respiratory system and COPD pathogenesis. We address the insufficiency of current COPD treatment as antioxidants and discuss future directions in COPD therapeutics targeting oxidative stress while avoiding side effects such as tumorigenesis.